Potential Benefits of TNF Targeting Therapy in Blau Syndrome, a NOD2-Associated Systemic Autoinflammatory Granulomatosis - Matsuda, Tomoko; Kambe, Naotomo; Takimoto-Ito, Riko; Ueki, Yoko; Nakamizo, Satoshi; Saito, Megumu K.; Takei, Syuji; Kanazawa, Nobuo (Frontiers in Immunology, 2022)
Blau syndrome is a systemic autoinflammatory granulomatous disease caused by mutations in the nucleotide-binding oligomerization domain 2 (NOD2) gene. NOD2 is an intracellular pathogen recognition receptor. Upon binding to muramyl dipeptide (MDP), NOD2 activates the NF-κB pathway, leading to the upregulation of proinflammatory cytokines. Clinical manifestations of Blau syndrome appear in patients before the age of four. Skin manifestations resolve spontaneously in some cases; however, joint and eye manifestations are progressive, and lead to serious complications, such as joint contracture and blindness. Currently, there is no specific curative treatment for the disease. Administration of high-dose oral steroids can improve clinical manifestations; however, treatments is difficult to maintain due to the severity of the side effects, especially in children. While several new therapies have been reported, including JAK inhibitors, anti-IL-6 and anti-IL-1 therapies, anti-TNF therapy plays a central role in the treatment of Blau syndrome. We recently performed an ex vivo study, using peripheral blood and induced pluripotent stem cells from patients. This study demonstrated that abnormal cytokine expression in macrophages from untreated patients requires IFNγ stimulation, and that anti-TNF treatment corrects the abnormalities associated with Blau syndrome, even in the presence of IFNγ. Therefore, although the molecular mechanisms by which the genetic mutations in NOD2 lead to granuloma formation remain unclear, it is possible that prior exposure to TNFα combined with IFNγ stimulation may provide the impetus for the clinical manifestations of Blau syndrome.